1999
DOI: 10.1161/01.cir.100.13.1443
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells Cause Apoptosis of Cardiomyocytes and Proliferation of Other Intramyocardial Cells In Vitro

Abstract: Mast cells cause apoptosis of cardiomyocytes and proliferation of other intramyocardial cells via the activity of RMCP 1. Our results suggest that mast cell chymase may play a role in the progression of heart failure, because loss of cardiomyocytes and proliferation of nonmyocardial cells exaggerate its pathophysiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
77
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 27 publications
1
77
0
1
Order By: Relevance
“…21,22 Mast cell chymase induces the proliferation of cardiac fibroblasts and apoptosis of cardiac myocytes. 16 We have previously reported that IL-1 , a prominent cytokine in cardiac remodeling, is upregulated in the chronic stage of EMC viral myocarditis, 27 and it has also been implicated in fibrosis after myocardial infarction. 28 The human mast cell chymase, the counterpart of mMCP-5, which was upregulated in the present study, converts the precursor IL-1 to an active form, 15 suggesting that mMCPs play a role in cardiac remodeling.…”
Section: Discussionmentioning
confidence: 97%
“…21,22 Mast cell chymase induces the proliferation of cardiac fibroblasts and apoptosis of cardiac myocytes. 16 We have previously reported that IL-1 , a prominent cytokine in cardiac remodeling, is upregulated in the chronic stage of EMC viral myocarditis, 27 and it has also been implicated in fibrosis after myocardial infarction. 28 The human mast cell chymase, the counterpart of mMCP-5, which was upregulated in the present study, converts the precursor IL-1 to an active form, 15 suggesting that mMCPs play a role in cardiac remodeling.…”
Section: Discussionmentioning
confidence: 97%
“…39 Protease-induced apoptosis is not a specific phenomena for chymase and SMCs, inasmuch as elastase and proteinase 3 (neutrophil serine proteases) can induce the apoptosis of endothelial cells, 40 ␣-chymotrypsin and trypsin can induce the apoptosis of neutrophils, 41 and chymase can induce the apoptosis of cardiomyocytes. 42 However, the observation that granule-bound natural chymase can induce apoptosis, even in the presence of natural inhibitors, might support a role for mast cell-derived granule-bound chymase compared with other neutral proteases at the site of atherogenesis in inducing apoptosis in vivo. Interestingly, peripheral blood monocytes, lymphocytes, several human leukemic cell lines (THP-1, HL-60, and K562), murine L929 fibroblasts, mouse perito- neal macrophages, 41 and myocardial fibroblasts 42 failed to undergo apoptosis after treatment with proteases, suggesting that cells also differ in their susceptibility to undergo protease-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…42 However, the observation that granule-bound natural chymase can induce apoptosis, even in the presence of natural inhibitors, might support a role for mast cell-derived granule-bound chymase compared with other neutral proteases at the site of atherogenesis in inducing apoptosis in vivo. Interestingly, peripheral blood monocytes, lymphocytes, several human leukemic cell lines (THP-1, HL-60, and K562), murine L929 fibroblasts, mouse perito- neal macrophages, 41 and myocardial fibroblasts 42 failed to undergo apoptosis after treatment with proteases, suggesting that cells also differ in their susceptibility to undergo protease-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1 mRNA levels were unchanged initially, but increased markedly between 48 and 72 h after I/R in WT hearts (Table S4). In 72-h post-I/R hearts, IGF-1 mRNA was enriched in cardiomyocytes (relative expression: 1 ± 0.22 versus 0.27 ± 0.027 18 S-normalized IGF-1 mRNA transcripts in cardiomyocytes and noncardiomyocytes, respectively, n = 3, P < 0.05), suggesting that these cells are the main source of IGF-1 production. In contrast to IGF-1 mRNA levels, cardiac IGF-1 protein levels fell by 35% between 48 and 72 h after I/R (P < 0.001) (Fig.…”
Section: Beneficial Effects Of Mcpt4 Deletion In Postischemic Hearts Arementioning
confidence: 94%
“…2 A-C) and could be due to late preservation of myocardium after I/R through a suppression of deleterious effects of MMCP-4 on cardiomyocyte survival. We considered this possibility because prior in vitro work has shown that mast cell serine proteinases cause cultured rat neonatal cardiomyocyte to undergo apoptosis (18); albeit that the apoptosis mechanism was not explored.…”
Section: Beneficial Effects Of Mcpt4 Deletion In Postischemic Hearts Arementioning
confidence: 99%